The Kansei Engineering and its Approaches - Margolis Ribeiro, Iara; Providência, Bernardo (InfoDesign, 2021)
Kansei Engineering emerged in the 1950s as a product development technology through intangible perceptions, such as the user’s feelings about a good or service. It is a methodology that seeks to embody the feeling in a physical design, or even service improvements, through various and different practical approaches. In the published material it is possible to notice an evolution and a growth of the practices adopted from the use of the word Kansei to the use of mathematical modeling or virtual reality. This article aims to concatenate the types of approaches under the bias of several authors in the field. Thus, this work aimed to analyze the origin of Kansei engineering and its different types of methods used. The article brings together, from a bibliographic analysis work, a total of eight different types of methods. A comparison is made between the methods and their characteristics, as well as the particularities of each type.